Modern Film Dramaturgy An Introduction - Stutterheim, Kerstin (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
What makes a good movie? How can one analyse a film accordingly without primarily interpreting it? Dramaturgy can enrich film understanding, for those who make films, as well as for those who want to understand better why they are made how. Film Dramaturgy supports the creative process of filmmaking, especially the work of the authors, directors and producers. Students and professionals who are involved in the creation of a film also benefit from this knowledge. The understanding of dramaturgy supports film analysis and film criticism too. In some regions of the world, dramaturgy is well established; in other parts, it is less familiar. This book provides a basic introduction to modern film dramaturgy. It emerges from academic research drawn from professional practice. It addresses students, scholars, colleagues, filmmakers and all professionals involved in making films, videos, audio-visual time-based media productions.